Aesthetics, digital studies and Bernard Stiegler - Fitzpatrick, Noel, 1967 December 27-; O'Dwyer, Néill, 1979-; O'Hara, Mick (Michael) (Bloomsbury Academic, 2021)
"A collection of philosophical and aesthetic essays, influenced by Bernard Stiegler, which focuses on the techno-cultural artefact in order to critique, engage, or respond to, an aspect of digital culture"-- Provided by publisher.
Keywords: Stiegler, Bernard -- Influence.; Stiegler, Bernard; Digital media -- Philosophy.; Technology -- Philosophy.; Aesthetics.; Médias numériques -- Philosophie.; Technologie -- Philosophie.; Media studies.; Aesthetics; Digital media -- Philosophy; Influence (Literary, artistic, etc.); Technology -- Philosophy